Competition, Barriers to Entry and Inclusive Growth in Retail Banking: Capitec Case Study - Makhaya, Trudi; Nhundu, Nicholas (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2016)
This case study examines barriers to entry in retail banking in South Africa, informed by Capitec’s experiences as an entrant in this concentrated and highly regulated sector. Capitec’s entry and growth in transactional banking sparked a competitive response from incumbents. Across all four incumbent banks, the fees for low-cost accounts have come down in nominal terms. It is unlikely that these effects would have occurred if the status quo had continued without a disruptive entrant, or if Capitec had been acquired by one of the incumbents early on. Capitec overcame barriers to entry including customers’ reluctance to switch, complex regulation, and the largely self-regulated payments system, in order to grow, in a sector populated by incumbents with some market power. The case study considers measures that could lower barriers for future entrants.